2020
DOI: 10.21037/jtd.2020.04.36
|View full text |Cite
|
Sign up to set email alerts
|

Fixed in the neck or pushed back into the thorax?—Impact of cervical anastomosis position on anastomosis healing

Abstract: Contributions: (I) Conception and design: YD Lin; (II) Administrative support: YD Lin; (III) Provision of study materials or patients: YD Lin;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Generally, surgical resection is a preferred treatment option for tumor patients. For esophageal cancer patients, left neck anastomosis is usually combined with tumor resection to rebuild the digestive tract and provide conditions for postoperative nutritional support ( 3 ). At present, placement of feeding nutritional applicators carrying ^(125)I particles is a relatively novel treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, surgical resection is a preferred treatment option for tumor patients. For esophageal cancer patients, left neck anastomosis is usually combined with tumor resection to rebuild the digestive tract and provide conditions for postoperative nutritional support ( 3 ). At present, placement of feeding nutritional applicators carrying ^(125)I particles is a relatively novel treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…After investigating factors affecting gastro-esophageal cervical anastomotic leakage, Luo et al found that cervical anastomosis fixation, hypertension, and anastomosis mode are independent risk factors. [ 3 ] In their study, cervical gastro-esophageal anastomosis was performed either with hand sewing or with a circular stapler, and the anastomosis was either fixed in the neck by sewing to the adjacent cervical muscles or pushed back in to the thoracic cavity. Pushing the anastomosis back into the thoracic cavity had significantly lowered the incidence of anastomotic leakage compared with the anastomosis being fixed in the cervical muscle (4.4% vs 11.4%, P = .027), because pushing the anastomosis back into the thorax could improve both the arterial blood perfusion and venous blood flow return theoretically.…”
Section: Discussionmentioning
confidence: 99%
“…Pushing the anastomosis back into the thoracic cavity had significantly lowered the incidence of anastomotic leakage compared with the anastomosis being fixed in the cervical muscle (4.4% vs 11.4%, P = .027), because pushing the anastomosis back into the thorax could improve both the arterial blood perfusion and venous blood flow return theoretically. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations